(3QSGdI aj GdcGahQs - (3CHh Ydj CMeO Hf YHO GdQMef, GHf efOhjg GdCUagGfj,J (B372 (3g` s
(3ChdgG (B:s
(3bGd CHh Ydi Mb eG bjd hScJ ef dGjYde jSbW aGfG Cf bO Ydeg hdMb eG SHb LGdjfhS fMPQ GdeJYdejf Ef jSHbhG Edi EYJbGO GdQCi s
(3BNQgG (B:s
(3aUGQ dPdc GdcGahQ ai GdZGjI GdbUhi Ydi bWY GdHGg hJYWjd BdGJgG agPG eG MVQfi ef Gdbhd ai GdcGahQ hGddg hdi GdJhajb hGdEQTGO JeJ s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdKGdKI YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B885s
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGi (B(568) s
Keywords: (3GdWHs